Impact of six versus 12 months of dual antiplatelet therapy in patients with drug‐eluting stent implantation after risk stratification with the residual SYNTAX score: Results from a secondary analysis of the I‐LOVE‐IT 2 trial. (17th February 2017) - Qiu, Miaohan; Li, Yi; Li, Jing; Xu, Kai; Jing, Quanmin; Dong, Shaohong; Jin, Zhe; Zhao, Pitian; Xu, Bo; Han, Yaling
Abstract : Background: The optimal duration of dual antiplatelet therapy (DAPT) after drug‐eluting stent (DES) implantation remains undetermined, especially for those at high risk of cardiac events postprocedure. Objectives: This study was aimed to investigate the impact of 6 versus 12 months of DAPT after DES implantation based on risk stratification with the residual SYNTAX score (rSS). Methods: A total of 2737 patients in the I‐LOVE‐IT 2 trial were grouped according to rSS status (low rSS [rSS = 0, n  = 1474] versus high rSS [rSS > 0, n  = 1263]) and DAPT duration (6 months vs. 12 months). The primary endpoint was 12‐month target lesion failure (TLF), and the major secondary endpoints were 12‐month net adverse clinical events (NACE) and major bleeding. Results: Incidences of TLF (5.2 vs. 7.4%, P  = 0.01) and NACE (9.2 vs. 13.4%, P  < 0.001) at 12 months were significantly higher in patients with high rSSs compared with patients with low rSSs. Landmark analysis showed that, in patients with high rSS, 12‐month DAPT was associated with slightly lower risks of TLF (3.0% vs. 1.6%, P  = 0.08) and NACE (7.0 vs. 4.4%, P  = 0.054) compared with 6‐month DAPT within 6 to 12 months after PCI. Patients with different DAPT durations had similar risks of bleeding both in the low and high rSS groups. Conclusions: Patients with high rSSs have an increased risk of TLF and NACE at 12 months after DES implantation. Twelve‐month DAPT might be superior to 6‐month DAPT in patients with high rSS for reducing adverse events within 6 to 12 months after PCI without excessive risk of bleeding. © 2017 Wiley Periodicals, Inc.